Exchange coupling and energy product in random two-phase aligned magnets. - COEY, JOHN MICHAEL DAVID (IEEE, 1994)
Size effects in two-phase Boolean magnets composed of an aligned hard phase and a soft phase with high magnetization are investigated. In 'overcritical' magnets, where the size of the soft regions is larger than the Blochwall width ??h of the hard phase, the energy product is reduced compared to the corresponding 'undercritical' magnets with small soft regions, where theoretical energy products as high as 1 MJ/m3 have been predicted. Nevertheless, the theoretical energy product only gradually drops with increasing size of the soft regions, and it may still exceed the theoretical energy product 516 kJ/m3 of Nd2Fe14B.
PUBLISHED
Keywords: Physics